Prognostic evaluation of mucin-5AC expression in intrahepatic cholangiocarcinoma, mass-forming type, following hepatectomy. Issue 11 (November 2015) - Abe, T.; Amano, H.; Shimamoto, F.; Hattori, M.; Kuroda, S.; Kobayashi, T.; Tashiro, H.; Ohdan, H.
Abstract: Aim: This study aimed to investigate the clinicopathological predictors of survival in patients with intrahepatic cholangiocarcinoma, mass-forming type (ICC-MF), following curative intent hepatectomy. Methods: Clinical characteristics and outcomes were analyzed in a series of 42 patients who underwent curative hepatectomy for ICC-MF between February 1987 and December 2012. The relationship between immunohistochemical expression profiles of mucin (MUC) core proteins (MUC2, MUC5AC, and MUC6) and surgical outcomes was examined. Results: The overall median follow-up period was 2.6 years (0.2–17.9). Bile duct reconstruction ( p  = 0.017), lymph node metastasis ( p  = 0.049), maximal mass diameter ≥5.0 cm ( p  = 0.002), and MUC5AC expression ( p  = 0.003) were identified as significant adverse predictors of overall survival by univariate analysis. Bile duct reconstruction ( p  = 0.048), maximal mass diameter ≥5.0 cm ( p  = 0.002), and MUC5AC expression ( p  = 0.005) were found to be independent predictors of poor prognosis by multivariate analysis. Maximal mass diameter ≥5.0 cm ( p  = 0.011) was found to be an independent predictor for the tumor recurrence. There was a strong correlation between MUC5AC expression and lymph node metastasis ( p  = 0.021). MUC6 expression was more frequent in patients with concurrent MUC5AC expression ( p  = 0.019). Conclusions: MUC5AC expression was significantly related to long-term prognosis and aggressive tumor development, and may be a useful prognostic marker.